Struktur Komunitas Arthropoda Dalam TanahPada Areal Perkebunan Karet (Hevea bransiliaensis) Di Kec. InumanKab. Kuantan Singingi - Riau - Febrita, Elya; Mayrita, Eka (Jurnal Pilar Sains, 2008)
Have been done the research to know the community structure of deep soil Arthropoda in the rubberplantation Hevea bransiliaensis) area at Inuman district, Kuantan Singingi, which is conducted on Octoberuntil December 2006. the point of the research station was held based on purposive random sampling whichis shown that age of the rubber are 1 year, than 5 years and last 10 years and the areas about 100 x 100 mlarge. The Arthropoda is held by applying dinamical method which use Barles Tulgreen. The parameters use: physics and chemist that talk about pH, temperature, water content of soil, organic material of soil and soiltexture, while biology are composition, domination index, diversity index, equitability index and distributionindex. The result of research shows Arthropoda composition deep soil is about 7 ordo, 11 species and 344individual, in which Hymenoptera and Collembolla ordo was plentiful found. The lower domination is about0,1274 - 0,2271, it means that there no animal dominated, the diversity is about 1,6637 - 2,2021, is means theamounts of species personal are not various, the higher aquatability is about 0,7676 - 0,9193, so it means thatthe spread of individu are fixed and no domination. The Arthropoda variety on the ground in piece A (0 -15cm) is higer than piece B (15 - 30 cm). The vertical distribution on the three station shows the clumpeddistribution.Key words : Deep soil Arthropoda, Community structure, Hevea bransiliaensis plantation",